Immersive 3D simulation therapy for acrophobia / Nazirul Mubin Mohamed - Mohamed, Nazirul Mubin (2014)
Virtual Reality therapy (VRT), dependent upon this modern innovation, has been as of late utilized as a part of the medication of subjects diagnosed with acrophobia, a phobia that is described by marked anxiety upon exposureness to heights .Conventional VR frameworks for the medication of acrophobia have limits, over-excessive cost or to some degree unlikely realistic graphics. The objective of this study was to improve a cheap and more realistic virtual environment (VE) in which to perform introduction treatment for acrophobia. It is based on computer, and a virtual scene of a open room located on the highest level of a high building. The virtual situation incorporates an open lift encompassed by props by the side of a tower, which permits the patient to feel a feeling of heights. The viability of the VE was assessed through the clinical medicine of a subject who was experiencing the fear. Subsequently, it was demonstrated that this VR environment was adequate and reasonable at succeeding acrophobia agreeing not just to the examination comes about of assortment of questionnaires prior and then afterward medication additionally to the subject's remarks that the VE appeared to inspire more fearful emotions than the true situation.